Structural vector autoregressions with nonnormal residuals - Markku Lanne; Helmut Lütkepohl (Center for Economic Studies and ifo Institute (CESifo), 2006)
In structural vector autoregressive (SVAR) models identifying restrictions for shocks and impulse responses are usually derived from economic theory or institutional constraints. Sometimes the restrictions are insufficient for identifying all shocks and impulse responses. In this paper it is pointed out that specific distributional assumptions can also help in identifying the structural shocks. In particular, a mixture of normal distributions is considered as a plausible model that can be used in this context. Our model setup makes it possible to test restrictions which are just-identifying in a standard SVAR framework. In particular, we can test for the number of transitory and permanent shocks in a cointegrated SVAR model. The results are illustrated using a data set from King, Plosser, Stock and Watson (1991) and a system of US and European interest rates.
Keywords: C32; 330; mixture normal distribution; cointegration; vector autoregressive process; vector error correction model; impulse responses; VAR-Modell; Kointegration; Fehlerkorrekturmodell; Theorie